Quality of life analysis of fixed orthodontic treatment by denturists - Wardhana, Erdianto Setya; Suhartono, Budi; Pragola, Syadza Bethari (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Riskesdas data in 2018 showed a 57.6% dental and oral problems prevalence. One of the abnormalities of the teeth and mouth is malocclusion. Malocclusion can be fixed by performing orthodontic treatments performed by orthodontist dentists. However, because orthodontic care requires a considerable cost, those with low economy and education look for alternatives by performing orthodontic treatments to dental artisans. Objectives: This study evaluates the patient's quality of life (QoL) with fixed orthodontic treatment by dental artisans (denturists) using the OHIP-14 questionnaire.Methods: The research method used is descriptive observational, where samples are taken by random sampling of the 67 patients who used fixed orthodontic treatment by denturists. This research applied a cross-sectional study conducted by collecting data only using the OHIP-14 questionnaire at a time without further investigation. The data analysis applied was the Univariate Statistical test.Results: The results of the total score obtained from the dimensions of functional limitations are 238 (moderate category), physical pain is 220 (moderate category), psychological discomfort is 205 (moderate category), physical disability is 232 (moderate category), psychological disability is 225 (moderate category), social disabilities is 230 (moderate category), the barriers is 246 (bad category).Conclusion: Several factors caused denturists' impaired QoL of patients in fixed orthodontic treatment, with six as moderate categories and one as poor.